A Highly Sensitive Fluorogenic Probe for Imaging Glycoproteins and Mucine Activity in Live Cells in the Near-Infrared Region - Samaniego Lopez, Cecilia (2018)
A novel fluorescent molecular probe is reported, which is able to detect glycoproteins, especially mucins, with high sensitivity and with a turn-on response along with a large Stokes shift (>130 nm), within the biologically active window. The probe contains an aminotricarbocyanine as the fluorescent reporter with a linked benzoboroxole as the recognition unit, which operates through a dynamic covalent reaction between the boronic hemiester residue of the receptor and cis-diols of the analyte. The superior selectivity of the probe is displayed by the labeling of mucins present in Calu-3 cells. The new benzoboroxole fluorescent derivative gathers together key properties to make it a highly rated molecular probe: specificity, excellent solubility in water, and off–on near infrared emission. This probe is expected to be an excellent tool for imaging intracellular mucin to evaluate mucus-related diseases as well as a sensing strategy towards glycosylated structures with a high potential for theranostics approaches in biological samples.